2016
DOI: 10.1021/acs.nanolett.6b03119
|View full text |Cite
|
Sign up to set email alerts
|

Passivated Single-Crystalline CH3NH3PbI3 Nanowire Photodetector with High Detectivity and Polarization Sensitivity

Abstract: Photodetectors convert light signals into current or voltage outputs and are widely used for imaging, sensing, and spectroscopy. Perovskite-based photodetectors have shown high sensitivity and fast response due to the unprecedented low recombination loss in this solution processed semiconductor. Among various types of CHNHPbI morphology (film, single crystal, nanowire), single-crystalline CHNHPbI nanowires are particularly interesting for photodetection because of their reduced grain boundary, morphological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
297
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(315 citation statements)
references
References 45 publications
7
297
4
Order By: Relevance
“…Special micromorphologies such as 2D nanoplates, 1D NWs, 0D nanocrystals, nanonets, and inverse opals‐type structures have been carefully studied and showed superior optical properties and excellent electrical characteristics 52, 53, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. These structures will be discussed in detail in the following sections.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…Special micromorphologies such as 2D nanoplates, 1D NWs, 0D nanocrystals, nanonets, and inverse opals‐type structures have been carefully studied and showed superior optical properties and excellent electrical characteristics 52, 53, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. These structures will be discussed in detail in the following sections.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…However, owing to large specific surface area, defect‐free single crystal and high crystal quality. Photodetectors composed of nanowires and nanorods have higher response speed than those of the conventional single crystal photodetectors . Until now, several research groups obtained the μs‐level response speed using nanowire or nanorod structures respectively.…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
“…Polarz et al 26 developed metal–organic porous single-crystalline MAPbI 3 and also did not observe the (10) spots. Furthermore, Tang et al 27 , Vela et al 28 , and Zhu et al 29 found that the {110} spots were missing in MAPbI 3 nanowires. Segawa 30 explained that the (110) and (10) diffraction spots are inherently difficult to be detected experimentally due to the low ED intensity of organic–inorganic halide compounds.…”
Section: Introductionmentioning
confidence: 99%